A Profile of JAMIS Publications between 2006 and 2012. Reflections on the Journey towards Internationalization - Nadia Albu; Camelia Iuliana Lungu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The aim of this paper is to provide an overview of the publications in the Journal of Accounting and Management Information Systems (JAMIS) over the period 2006-2012, and to comment on their characteristics in the context of international practices and of the Romanian particularities. We use observation and statistical analysis of the characteristics of the 175 articles in terms of authorship, citations, topics, and methodologies. We find that JAMIS is a journal that covers various aspects in terms of articles' methodology, topics, and authors' affiliation. A trend towards increasing the length of the papers and the number of references was found, suggesting an increasing in the quality of the papers published in JAMIS over this period. Our analysis is intended to provide an overview to an international audience about the transformations of a journal originated in an emerging economy, from a local orientation towards internationalization, and to inform current and potential authors about the characteristics of the publications in this journal.
Keywords: M41; M40; 650; JAMIS; methodologies; research; academic journals